Determinants of hypermarket selection decision: A study at Mydin MITC Hypermarket Ayer Keroh, Melaka / Jamal Mohamed Sapari and Mohamad Haikal Syamir Hamid - Mohamed Sapari, Jamal; Hamid, Mohamad Haikal Syamir (Faculty of Administrative Science and Policy Studies, 2014)
The study seeks to identify the determinants of hypermarket selection decision. A sample 315 customers at Mydin MITC Hypermarket, Ayer Keroh, Melaka had been selected for this study. The findings showed that the independent variables or factors that support the researchers’ hypothesis are variety of product, price of product, quality of product, services by hypermarket, and location of hypermarket. All five factors determine their relationship with the factors that influence hypermarket selection decision among customer at Mydin MITC Hypermarket, Ayer Keroh, Melaka. Convenient sampling technique will be used in order to distribute the questionnaires to the selected respondents. Based on the finding, service by hypermarket is the most contributing factor that influences hypermarket selection decision. While, all the five factors (variety of product, price of product, quality of product, services by hypermarket, and location of hypermarket) have a significant relationship with the hypermarket selection decision. This is due to the result of correlation coefficient that has been used. In conclusion the study has been successfully implemented and shows that five factors have a relationship with hypermarket selection decision.